Investigation and Optimization of a Line-Locked Quartz Enhanced Spectrophone for Rapid Carbon Dioxide Measurement - Hui Zhang; Wenling Jin; Mengpeng Hu; Mai Hu; Jingqiu Liang; Qiang Wang (Sensors, 2021)
We have developed a rapid quartz enhanced spectrophone for carbon dioxide (CO2) measurement, in which the laser wavelength was tightly locked to a CO2 absorption line and a custom quartz tuning fork (QTF) operating at 12.5 kHz was employed. The intrinsic QTF oscillation-limited response time, as well as the optimal feedback interval, was experimentally investigated. By tightly locking the laser to the R(16) transition of CO2, we obtained a stable laser operation with its center wavelength variation kept within 0.0002 cm−1, merely three times the laser linewidth. The reported CO2 sensor achieved a detection limit of 7 ppm, corresponding to a normalized noise equivalent absorption coefficient (NNEA) of 4.7 × 10−9 W·cm−1·Hz−1/2, at a response time of 0.5 s. The detection limit can be further improved to 0.45 ppm at an integration time of 270 s, illustrating a good system stability. This spectrophone enables the realization of compact and fast-response gas sensors for many scenarios, where CO2 concentration from sub-ppm to hundreds of thousands of ppm is expected.